Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament (Cape Town Government Printers, 1976)
South Africa Parliament House of Assembly. Debates of the House of Assembly (Hansard). Debates of Standing Committees.
South Africa. Parliament. House of Assembly. Debates of Standing Committees published annually and parallel with Afrikaans title. Merged with: Debates of the House of Delegates, and; Debates of the House of Representatives, to form: Debates of Parliament. 139 v. 22 cm.
Keywords: Indexes to Debates; House of Assembly; Third Session; Fifth Parliament; January; June; Vol. 65; ISBN 0621031194; Index to Questions; JC045360